IMPROVING THE METHODOLOGY OF TEACHING MOLECULAR PHYSICS IN HIGHER EDUCATION BASED ON ELECTRONIC LEARNING RESOURCES - M.M. Quchqorova (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract This study examines the methodological foundations for improving the teaching of molecular physics in higher education through the integration of electronic learning resources (ELRs). The research highlights the role of digital technologies, virtual laboratories, and interactive simulations in enhancing students’ conceptual understanding of microscopic physical processes. The paper proposes a model for integrating ELRs into the curriculum and evaluates its effectiveness through pedagogical analysis. The results demonstrate that the use of ELRs significantly improves students’ engagement, independent learning skills, and academic performance.